Toward coupling color centers in single crystal diamond to two-dimensional materials - Opaluch, Oliver; Nelz, Richard; Challier, Michel; Radtke, Mariusz; Slablab, Abdallah; Xu, Zaiquan; Aharonovich, Igor; Neu, Elke (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Individual nitrogen vacancy (NV) color centers in diamond are bright, photo-stable, atomic-sized dipole emitters [1]. Consequently, they represent optimal candidates for novel scanning near field microscopy techniques [2]. Here, NV centers form one member of a Forster Resonance Energy Transfer (FRET) pair. Due to their broadband emission (> 100 nm), NVs are versatile donors for FRET to systems absorbing in the near infrared spectral range. Highly-promising applications include, e.g., nanoscale imaging of fluorescent molecules or nanomaterials like graphene [2].
CRIS-Team Scopus Importer:2023-03-27